Education in Juvenile Detention Facilities in the State of Connecticut: A Glance at the System - Macomber, Donna (J Correct Educ (Glen Mills), 2010)
The state of Connecticut detained 7,444 children and youth and committed approximately 270 to the Department of Children and Families for out of home placement in the 2007-2008 calendar year. A significant number of children and youth have special education needs that are often unidentified by home school districts. State and federal law mandate the provision of special education and related services to this population. In addition, education of these individuals is imperative as research indicates educational success is a key component for decreasing recidivism (relapse into unlawful activity) rates and providing opportunities toward productive adulthood. The cost of recidivism to detention is not only monetary; criminal misconduct also threatens the safety of society members as well. The Yale University Child Study Center under the auspices of the Connecticut Judicial Branch, Court Support Services Division (CSSD) conducted a situational analysis of the juvenile detention centers and community residential centers. The focus of this analysis was to: (1) describe the educational characteristics of detained children and youth; (2) describe the educational programs currently used in detention and assess whether the educational programming provided is consistent with the framework of the State of Connecticut Department of Education; (3) typify the community of teachers working with students in detention, identify systemic obstacles and/or challenges to educating this population, ascertain the pathways of educational records of detained children and youth; and (4) identify system barriers or challenges to delivering education to this population and teaching in detention or alternative to detention settings. This report is a summary of findings.